Double cross hibrids produced with lines improved by gamete and backcross selection. - Navarro, Enrique; Burciaga, Gustavo; González, Salvador; Vega, M. Cristina; Morones, Regino; Sandoval, Elias (Agronomía Mesoamericana, 2016)
This research work includes the evaluation of 1040 double cross hybrids which were produced from single crosses improved by gamete and backcross procedures. Single hybrids were crossed with five testers. The yield trials were carried out during 1991 at Gómez Palacio, Durango, México, and the goals were as follows: 1) To evaluate the performance of double cross hybrids and 2) To determine the main agronomic traits on the observed variation. For grain yield, the double cross hybrids formed with single crosses improved by gamete selection performed better than those obtained by backross whose yields were adobe 11,6 t/ha (23% with respect to the best backcross genotype). The outstanding yields observed across the gamete procedure are probably due to the low percentage of rot ers. On the controry, the single crosses improved by backcross procedure showed early to flower, short height and had less problems ofboth root and stalk lodging. The best testers were AN258-18-19 x MLS4-1 and the AN 232 x 255- 18-19 when crossed with some single crosses yield more than 14 t/ha. It is import to mention that the outstanding grain yields were associated with values of general combining ability with the gamete selection. Finally, the multivariate analysis showed that two-thirds of the observed variation in the double cross hybrids was given by grain yield and clean grain yield, plant and ear height, male and female flowering.